(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In French linguistics, like in all languages, the use of euphemism has been formed as a historical ethnographic phenomenon in connection with the phenomenon of taboo. Euphemism is associated with the development of customs, cultural levels, aesthetic tastes, and ethnic norms in nations. With the development of the language, its euphemistic layer also develops. This article explains the concepts of “euphemism” and “taboo”, their place, and their importance in linguistics, particularly in French linguistics.